Assessment of quality of life in patients with celiac disease and non-celiac gluten sensitivity on a gluten-free diet before and during the war in Ukraine - Denesyuk , Oleg; Gubska , Olena (The Ukrainian Scientific Medical Youth Journal, 2024)
the necessity of adhering to a gluten-free diet for individuals with celiac disease and non-celiac gluten sensitivity is a significant factor affecting their well-being. They experience social, economic, and medical (due to the absence of alternative treatment methods) pressures. The aim of the study was to investigate and compare the quality of life and adherence to a gluten-free diet among patients with celiac disease and non-celiac gluten sensitivity in Ukraine before and during full-scale invasion. The study included 24 adult participants, 15 with celiac disease and 9 with non-celiac gluten sensitivity. Demographic data (age and gender) and clinical characteristics of patients, symptoms, and monitoring of IgA antibodies (tTG-IgA) to determine disease activity were collected at the time of enrollment in the study. All participants were asked to complete the Celiac Disease Quality of Life Measure (CD-QoL) questionnaire, which helps assess the impact of celiac disease and adherence to a gluten-free diet on a person’s quality of life. Additionally, the quality of adherence to a gluten-free diet was assessed using the Biagi questionnaire. This study showed that patients with celiac disease and non-celiac gluten sensitivity in Ukraine have a low quality of life on a gluten-free diet according to the CD-QoL questionnaire. The average total CD-QoL score was 68.54 ±2.5. In detail, the score for disphoria subscale was 15.7 ±0.5, the score for food restrictions subscale was 30.3 ±1.3, the score for health concern subscale was 17.3 ± 0.8, and the score for treatment ineffectiveness subscale was 5.3 ±0.4. There was no statistically significant difference observed in dependence between men and women, patients with celiac disease and non-celiac gluten sensitivity, patients older and younger than 35 years, patients with positive and negative tTG-IgA antibodies, migrants and non-migrants, and based on the duration of following a gluten-free diet (p>0.05). However, it is worth noting that there is a trend towards better quality of life in male patients compared to female subjects (p = 0.07, Table 2). Also, a trend towards higher CD-QoL scores was observed in patients younger than 35 years compared to those older than 35 years (p = 0.06) and in patients with positive tTG-IgA antibodies compared to those with negative tTG-IgA antibodies (p = 0.07). In our opinion, this difference could become significant with the involvement of a larger number of study subjects. When comparing the CD-QoL questionnaire results before the full-scale invasion in Ukraine and during the war, a significant decrease in the quality of life according to the CD-QoL scale during the conflict period was found (p=0.000001). Considering these results, we believe that the CD-QoL questionnaire should be used in clinical practice to assess the quality of life of patients with celiac disease and non-celiac gluten sensitivity. This allows identifying factors that need to be addressed to improve adherence to a gluten-free diet and identifying aspects that require psychological support if necessary. The war has negatively affected the quality of life of patients with gluten-related disorders. In particular, we believe that patients over 35 years of age and patients who do not adhere well to a gluten-free diet require additional attention..